If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(5x + -9) + -3 = -4(2x + 5) + -6 Reorder the terms: -5(-9 + 5x) + -3 = -4(2x + 5) + -6 (-9 * -5 + 5x * -5) + -3 = -4(2x + 5) + -6 (45 + -25x) + -3 = -4(2x + 5) + -6 Reorder the terms: 45 + -3 + -25x = -4(2x + 5) + -6 Combine like terms: 45 + -3 = 42 42 + -25x = -4(2x + 5) + -6 Reorder the terms: 42 + -25x = -4(5 + 2x) + -6 42 + -25x = (5 * -4 + 2x * -4) + -6 42 + -25x = (-20 + -8x) + -6 Reorder the terms: 42 + -25x = -20 + -6 + -8x Combine like terms: -20 + -6 = -26 42 + -25x = -26 + -8x Solving 42 + -25x = -26 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 42 + -25x + 8x = -26 + -8x + 8x Combine like terms: -25x + 8x = -17x 42 + -17x = -26 + -8x + 8x Combine like terms: -8x + 8x = 0 42 + -17x = -26 + 0 42 + -17x = -26 Add '-42' to each side of the equation. 42 + -42 + -17x = -26 + -42 Combine like terms: 42 + -42 = 0 0 + -17x = -26 + -42 -17x = -26 + -42 Combine like terms: -26 + -42 = -68 -17x = -68 Divide each side by '-17'. x = 4 Simplifying x = 4
| 2.37=2y-2.93 | | 13x=80 | | x^4-28x^2+27=0 | | 3r+5r=1000 | | -8x-5(x-3)=15 | | 6(h-4)=5(h-3) | | x^2+1100x+100000=0 | | 16x-267x+22=44x-3 | | 18=42-x | | 12=3x+9x | | 14x+53=72-12 | | 5n-3.9=1.05 | | 2.5x+3y-4=0 | | x^2+18x=-65 | | x^2+18+65=0 | | (x-5)/4=1-x/5 | | 15x-6+2x-4=0 | | 7x+3*9=9+x*5 | | (x-5)/4=-x/5 | | 4.2m-5=3.4(m+2.5) | | 5.4=6l+3l | | 5.4=6l+l | | m=-0.6 | | 2y-8=10-y | | 5i+2i=2.17 | | 4+(2-q)4=8 | | 7*x+3*9=5*x | | 1n-14=3n | | 21+7x=9+x | | 16h+6h=88 | | x^2+18=-65 | | 12g+6g=54 |